Pemanfaatan Galon Bekas sebagai Pot Tanaman melalui Kegiatan Daur Ulang di Kelurahan Tempurejo (Proceedings of The National Conference on Community Engagement, 2026)
This community service activity aims to optimize the utilization of used water gallon containers as plant pots through recycling activities in Tempurejo Subdistrict, Pesantren District, Kediri City. The main problem addressed is the increasing volume of household plastic waste, particularly used gallons, which has not been managed optimally and poses potential environmental pollution. The method applied in this program is Participatory Action Research (PAR), which actively involves the community throughout the stages of planning, implementation, and evaluation. The activities include collecting used gallons through the local waste bank, cleaning and modifying the gallons into plant pots, and conducting ornamental plant planting activities involving children and local residents. The results indicate that used gallons can be effectively transformed into functional, economical, and aesthetically valuable planting media, while simultaneously reducing plastic waste in the residential environment. Furthermore, this activity enhances community awareness and concern for waste management based on the principles of Reduce, Reuse, and Recycle (3R), and encourages active community participation in sustaining environmental preservation.